Terapi Hipnosis 5 Jari Sebagai Upay Peningkatan Perkembangan Psikososial Lansia Agar Sehat Berintegritas Dan Bahagia - Diyan Mutyah; Hidayatus S; Dya Sustrami; Lela Nurlela; Sukma Ayu (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
Elderly people have health problems in the form of decreased social activities that affect the ability of the elderly to be independent in daily activities such as going to the toilet, dressing up, eating and the emergence of aggressive behavior that can affect their physical and mental health (Barker S, 2019). The results of the observation showed that the elderly are considered a normal condition by society and family, and are not given treatment or action. This can indirectly affect the independence of the elderly in meeting the stages of psychosocial development of the elderly (integrity). Five-finger hypnosis therapy is effective in reducing anxiety and stress in the elderly. This therapy helps regulate vital signs, improve blood circulation, and relax muscles, thus having a positive impact on the mental and physical health of the elderly. The objectives of this study include increasing awareness and knowledge of the elderly in Kalang Anyar Village about the importance of living a healthy and happy life and being free from mental health problems with 5-finger hypnosis which is a self-thinking relaxation technique with self-hypnosis. The method used is counseling and direct 5-finger hypnosis therapy in overcoming mental problems in the elderly. It begins with an explanation in the form of counseling and how to do 5 finger hypnosis therapy: by identifying the causes, signs, symptoms and effects of elderly anxiety and providing examples of 5 finger hypnosis therapy and 1) instructing the elderly to position their bodies to relax, 2) taking 3 deep breaths until the elderly feel much more relaxed, 3) instructing the elderly to close their eyes, 4) instructing the elderly to link their thumbs to their index fingers, then imagine their limbs being so healthy, 5) Instructing the elderly to link their thumbs to their middle fingers, then imagine the times when you were able to do something meaningful for the people closest to you, 6) Instructing the client to link their thumbs to their ring fingers, then imagine the times when you were given something meaningful by the people closest to you, 7) Instructing the client to link their thumbs to their little fingers, then imagine the most beautiful place when you are with the people closest to you, 8) Instructing the patient to take a deep breath then open their eyes, 9) Instructing the client to repeat this technique until the client feels calm. This therapy is carried out for 10 minutes (Keliat, 2013).